Public, Private, People Partnership Framework For Developing Indonesian Smart City Infrastructure - Erlando SULISTIA; Kwang Woo NAM (International Journal of Environmental, Sustainability, and Social Science, 2022)
The development of smart cities is an essential aspect of sustainable cities, but this initiative demands many resources. To assist the development of smart cities, the public, private partnership (PPP) concept has proven to be particularly helpful. The inclusion of the people, as a new stakeholder, is introduced to the concept to form a revised public, private, people partnership (PPPP) concept, which can improve the efficiency of developing services in a smart city via bottom-up development. Introducing the new stakeholder to the PPP framework brings new challenges. Issues related to introducing the new stakeholder in Indonesia have been divided into three categories: low awareness and limited information about government projects, human resources limitations, and uncertainty concerning government projects. Two concrete solutions are proposed to overcome this barrier: an information-sharing platform and a living laboratory-based PPPP. The objectives of this paper were, first, to analyze the stage of PPPP development in Indonesia, and then to provide a solution to facilitate its implementation in Indonesia. Three stages were identified: predevelopment, development, and maturity. Information collected included the title, authors, methodology, results, and recommendations. Data sources were primarily Science Direct, Google Scholar, and Scopus. Three of which were based on the PPPP model.